Financial accounting : tools for business decision making - Kimmel, Paul D; Weygandt, Jerry J; Kieso, Donald E (Hoboken, N.J. : Wiley, 2007)
Gives instructors the technology they need to create an environment where students can reach their potential and experience academic success. This book features Accounting Across the Organization that places accounting issues within the context of students majors. It also includes content on Sarbanes Oxley and Corporate Governance.
Keywords: 9